Human Research Development for Purpose Drug Research Function Increasing Case Disclosure in the Jurisdiction of the Cirebon City Police - Wiharto, Bastian Dhira Octavianto; Nita, Surya; Nasution, Ingka Harsani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
The narcotics problem in Indonesia is still very high, including cases of narcotics abuse. This problem also occurs in the legal area of the Cirebon City Police with an increasing trend in drug abuse. However, at the same time there is a decrease in the number of P21 which implies a decline or other factors that influence member performance, both internal and external. Therefore, handling drugs is a special concern for various groups. Not only the state apparatus, including outside the apparatus are involved in handling drug cases. In particular, the National Police is the front guard in handling drug cases. In the East Belitung area, the Police have the authority to handle drug problems which are directly handled by the Narcotics Research Unit (Satresnarkoba) which is tasked with carrying out the guidance and guidance of investigative functions, investigations, supervision of investigations into criminal acts of abuse and illicit trafficking of drugs and their precursors, as well as guidance and counseling in the context of prevention and rehabilitation of victims of drug abuse.